A Human-Centered Approach to Assessment of Team Diversity in Multi-Version Software Development - Lilikovych, Serhii; Sokol, Volodymyr (My University, 2017)
The article proposes comprehensive approach to personal diversity level assessment of involved developers in order to improve efficiency of multi-version software development. The approach allows to build project teams with prede ned level of diversity intentionally. A common conceptual scheme of the approach is elaborated, an appropriate criteria and metrics to estimate personal diversity of target software products diversity are given, and future research work is outlined as well.
Keywords: human-centered; diversity; multi-version software; criteria; metrics